Higher triglyceride to high‐density lipoprotein cholesterol ratio increases cardiovascular risk: 10‐year prospective study in a cohort of Chinese adults. Issue 2 (3rd August 2019) - Chen, Zekai; Chen, Guanzhi; Qin, Hailun; Cai, Zefeng; Huang, Jianhuan; Chen, Haojia; Wu, Weiqiang; Chen, Zhichao; Wu, Shouling; Chen, Youren
Abstract: Aims/Introduction: A higher ratio of triglyceride to high‐density lipoprotein cholesterol (TG/HDL‐C) is considered as the independent risk index of cardiovascular (CV) events. However, cohort studies regarding this correlation are rarely reported, especially in the Chinese population. The aim of present study was to explore the relationship of the TG/HDL‐C ratio with CV risks among Chinese adults during 10‐year follow‐up period. Materials and Methods: We carried out a prospective study using data obtained from 96, 542 individuals in Kailuan, who were grouped through the median value (0.8533) of the TG/HDL‐C ratio. Adverse outcomes mainly referred to major CV events. We used the person‐years incidence and cumulative incidence to predict the morbidity. The risk of CV events was estimated through Cox proportional hazard models. Results: The mean age of the cohort was 51.5 ± 12.6 years, and 79.6% of participants were men. During a median follow‐up period of 9.75 years, 5, 422 major CV events occurred, including 1, 312 myocardial infarction cases and 4, 228 stroke cases. The cumulative incidence of myocardial infarction, stroke and total CV events was 1.36% (range 1.29–1.43%), 4.38% (range 4.25–4.51%) and 5.62% (range 5.47–5.76%), respectively. Compared with low the TG/HDL‐C ratio (≤0.8533) group, the high TG/HDL‐C ratio (>0.8533) group had higher morbidity of CV events. The hazard ratio of total CV events, stroke and myocardial infarction was 1.19 (95% CI 1.12–1.26), 1.11 (95% CI 1.03–1.18) and 1.50 (95% CI 1.33–1.70), respectively. Furthermore, the TG/HDL‐C ratio and major CV events had a line‐shaped relationship with each other. Conclusions: Among the Chinese population, a higher TG/HDL‐C ratio is correlated with an increased risk of major CV events. Abstract : This is the first large prospective cohort study regarding the association of the triglyceride to high‐density lipoprotein cholesterol (TG/HDL‐C) ratio with major cardiovascular events among Chinese individuals. Among the Chinese population, an elevated TG/HDL‐C ratio is associated with an increased risk of major cardiovascular events.